THE SYSTEM OF DEVELOPING THE ABILITY OF STUDENTS OF VOCATIONAL SCHOOLS FOR SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP - M. Atadjanov; Kadirov Hasanboy (Journals Park Publishing, 2022)
The draft of the President's decision "On additional measures for the development of the system of vocational training of students" was announced. On the introduction of a new system of vocational training of students in general secondary educational institutions of the Ministry of Public Education, Ministry of Higher and Secondary Special Education, Ministry of Economic Development and Poverty Alleviation proposals are accepted.